Investigating the effect of sparger configuration on the hydrodynamics of a full-scale membrane bioreactor using computational fluid dynamics. Issue 127 (14th December 2015) - Amini, Ershad; Mehrnia, Mohammad Reza; Mousavi, Seyyed Mohammad; Azami, Hamed; Mostoufi, Navid
Abstract : A three-phase computational fluid dynamics (CFD) simulation was carried out in a full-scale membrane bioreactor to investigate the effect of sparger configuration on various hydrodynamic parameters. Abstract : A three-phase computational fluid dynamics (CFD) simulation was carried out in a full-scale membrane bioreactor to investigate the effect of sparger configuration on various hydrodynamic parameters. In the first configuration the sparger was placed at the bottom of the bioreactor (Config. 1) and in the second configuration the sparger was located at the entrance of the module (Config. 2). CFD results showed that at the same aeration rate, higher cross-flow velocity between membranes and shear stress on membranes were achieved using Config. 1. In other words, lower aeration is required to obtain the same liquid circulation velocity in this configuration. It was shown that a much more homogeneous bubble distribution was obtained in Config. 1. Residence time distribution (RTD) in Config. 1 was shown to be closer to the plug-flow condition. Solid phase (biomass) distribution was more uniform in Config. 1.